Trends in prevalence of blindness and distance and near vision impairment over 30 years: an analysis for the Global Burden of Disease Study - Bourne, Rupert; Baig, Atif Amin; Bärnighausen, Till; Jonas, Jost B.; Panda-Jonas, Songhomitra (The lancet. Global health, 2021)
Background - To contribute to the WHO initiative, VISION 2020: The Right to Sight, an assessment of global vision impairment in 2020 and temporal change is needed. We aimed to extensively update estimates of global vision loss burden, presenting estimates for 2020, temporal change over three decades between 1990-2020, and forecasts for 2050. - Methods - We did a systematic review and meta-analysis of population-based surveys of eye disease from January, 1980, to October, 2018. Only studies with samples representative of the population and with clearly defined visual acuity testing protocols were included. We fitted hierarchical models to estimate 2020 prevalence (with 95% uncertainty intervals [UIs]) of mild vision impairment (presenting visual acuity ≥6/18 and <6/12), moderate and severe vision impairment (<6/18 to 3/60), and blindness (<3/60 or less than 10° visual field around central fixation); and vision impairment from uncorrected presbyopia (presenting near vision <N6 or <N8 at 40 cm where best-corrected distance visual acuity is ≥6/12). We forecast estimates of vision loss up to 2050. - Findings - In 2020, an estimated 43·3 million (95% UI 37·6-48·4) people were blind, of whom 23·9 million (55%; 20·8-26·8) were estimated to be female. We estimated 295 million (267-325) people to have moderate and severe vision impairment, of whom 163 million (55%; 147-179) were female; 258 million (233-285) to have mild vision impairment, of whom 142 million (55%; 128-157) were female; and 510 million (371-667) to have visual impairment from uncorrected presbyopia, of whom 280 million (55%; 205-365) were female. Globally, between 1990 and 2020, among adults aged 50 years or older, age-standardised prevalence of blindness decreased by 28·5% (-29·4 to −27·7) and prevalence of mild vision impairment decreased slightly (-0·3%, −0·8 to −0·2), whereas prevalence of moderate and severe vision impairment increased slightly (2·5%, 1·9 to 3·2; insufficient data were available to calculate this statistic for vision impairment from uncorrected presbyopia). In this period, the number of people who were blind increased by 50·6% (47·8 to 53·4) and the number with moderate and severe vision impairment increased by 91·7% (87·6 to 95·8). By 2050, we predict 61·0 million (52·9 to 69·3) people will be blind, 474 million (428 to 518) will have moderate and severe vision impairment, 360 million (322 to 400) will have mild vision impairment, and 866 million (629 to 1150) will have uncorrected presbyopia. - Interpretation - Age-adjusted prevalence of blindness has reduced over the past three decades, yet due to population growth, progress is not keeping pace with needs. We face enormous challenges in avoiding vision impairment as the global population grows and ages. - Funding - Brien Holden Vision Institute, Fondation Thea, Fred Hollows Foundation, Bill & Melinda Gates Foundation, Lions Clubs International Foundation, Sightsavers International, and University of Heidelberg.
GBD 2019 Blindness and Vision Impairment Collaborators: Rupert Bourne, Jaimie D Steinmetz, Seth Flaxman, Paul Svitil Briant, Hugh R Taylor, Serge Resnikoff, Robert James Casson, Amir Abdoli, Eman Abu-Gharbieh, Ashkan Afshin, Hamid Ahmadieh, Yonas Akalu, Alehegn Aderaw Alamneh, Wondu Alemayehu, Ahmed Samir Alfaar, Vahid Alipour, Etsay Woldu Anbesu, Sofia Androudi, Jalal Arabloo, Aries Arditi, Malke Asaad, Eleni Bagli, Atif Amin Baig, Till Winfried Bärnighausen, Maurizio Battaglia Parodi, Akshaya Srikanth Bhagavathula, Nikha Bhardwaj, Pankaj Bhardwaj, Krittika Bhattacharyya, Ali Bijani, Mukharram Bikbov, Michele Bottone, Tasanee Braithwaite, Alain M Bron, Zahid A Butt, Ching-Yu Cheng, Dinh-Toi Chu, Maria Vittoria Cicinelli, João M Coelho, Baye Dagnew, Xiaochen Dai, Reza Dana, Lalit Dandona, Rakhi Dandona, Monte A Del Monte, Jenny P Deva, Daniel Diaz, Shirin Djalalinia, Laura E Dreer, Joshua R Ehrlich, Leon B Ellwein, Mohammad Hassan Emamian, Arthur G Fernandes, Florian Fischer, David S Friedman, João M Furtado, Abhay Motiramji Gaidhane, Shilpa Gaidhane, Gus Gazzard, Berhe Gebremichael, Ronnie George, Ahmad Ghashghaee, Mahaveer Golechha, Samer Hamidi, Billy Randall Hammond, Mary Elizabeth R Hartnett, Risky Kusuma Hartono, Simon I Hay, Golnaz Heidari, Hung Chak Ho, Chi Linh Hoang, Mowafa Househ, Segun Emmanuel Ibitoye, Irena M Ilic, Milena D Ilic, April D Ingram, Seyed Sina Naghibi Irvani, Ravi Prakash Jha, Rim Kahloun, Himal Kandel, Ayele Semachew Kasa, John H Kempen, Maryam Keramati, Moncef Khairallah, Ejaz Ahmad Khan, Rohit C Khanna, Mahalaqua Nazli Khatib, Judy E Kim, Yun Jin Kim, Sezer Kisa, Adnan Kisa, Ai Koyanagi, Om P Kurmi, Van Charles Lansingh, Janet L Leasher, Nicolas Leveziel, Hans Limburg, Marek Majdan, Navid Manafi, Kaweh Mansouri, Colm McAlinden, Seyed Farzad Mohammadi, Abdollah Mohammadian-Hafshejani, Reza Mohammadpourhodki, Ali H Mokdad, Delaram Moosavi, Alan R Morse, Mehdi Naderi, Kovin S Naidoo, Vinay Nangia, Cuong Tat Nguyen, Huong Lan Thi Nguyen, Kolawole Ogundimu, Andrew T Olagunju, Samuel M Ostroff, Songhomitra Panda-Jonas, Konrad Pesudovs, Tunde Peto, Zahiruddin Quazi Syed, Mohammad Hifz Ur Rahman, Pradeep Y Ramulu, Salman Rawaf, David Laith Rawaf, Nickolas Reinig, Alan L Robin, Luca Rossetti, Sare Safi, Amirhossein Sahebkar, Abdallah M Samy, Deepak Saxena, Janet B Serle, Masood Ali Shaikh, Tueng T Shen, Kenji Shibuya, Jae Il Shin, Juan Carlos Silva, Alexander Silvester, Jasvinder A Singh, Deepika Singhal, Rita S Sitorus, Eirini Skiadaresi, Vegard Skirbekk, Amin Soheili, Raúl A R C Sousa, Emma Elizabeth Spurlock, Dwight Stambolian, Biruk Wogayehu Taddele, Eyayou Girma Tadesse, Nina Tahhan, Md Ismail Tareque, Fotis Topouzis, Bach Xuan Tran, Ravensara S Travillian, Miltiadis K Tsilimbaris, Rohit Varma, Gianni Virgili, Ya Xing Wang, Ningli Wang, Sheila K West, Tien Y Wong, Zoubida Zaidi, Kaleab Alemayehu Zewdie, Jost B Jonas, Theo Vos
Gesehen am 21.04.2021
Published Online: December 1, 2020